Antiviral activity of compounds isolated from marine sponges (2023)
Marine sponges have been used for the isolation and purification of compounds with therapeutic properties for human use. These compounds are used mainly against viruses because these microorganisms mutate and create resistance easily to available treatments. In the last 60 years, marine sponges have been the subject of scientific research, which have addressed the discovery of compounds with activity against Herpes Simplex Virus (HSV) such as Ara-A; the avarol used against Human Immunodeficiency Virus Type 1 (HIV-1) and calyceramides against Influenza Virus. This article present a review of the chemistry and mechanism of action of the compounds isolated from marine sponges that have shown antiviral activity, to encourage the search for new molecules or their modification in order to obtain several sources of drug production and antiviral treatments. This review found that in vitro cell models have been the most used techniques and the HSV and HIV-1 are the main microorganisms studied for the determination of the antiviral activity; finally, it was found that the biological activities are directly related to the structure of the compounds, especially when they are analogs of amino acids or nucleotides. © 2014 Universidad de Valparaiso. All rights reserved.